0535 Improvements in Quality of Life in Female Obstructive Sleep Apnea Patients using a Gender Specific Auto-adjusting Positive Airway Pressure Device. (12th April 2019) - Wimms, Alison; Benjafield, Adam; Martins, Dagmar; Willes, Leslee; Lips, Aline; Fietze, Ingo; Topfer, Volker; Woehrle, Holger
Abstract: Introduction: Gender differences have been reported in OSA. Females have more flow limitation, lower AHIs, shorter apneas, and less severe oxygen desaturations. A female specific APAP (fAPAP) treatment algorithm (AutoSet for Her, ResMed) has been developed to address these characteristics. Minimal data exists on how this device impacts quality of life. Methods: Female patients with AHI ≥ 15 were invited into this study. Participants completed 5 baseline questionnaires: FOSQ; PHQ9; ESS; CSFQ; and EQ-5D. Participants then used the fAPAP in the home environment. On treatment PSG and questionnaires were repeated after 3 months. Results: 97 patients were enrolled and 87 completed the study. The average age was 54.1 ± 9.8; BMI was 31.9 ± 5.59; and baseline AHI was 39.0 ± 17.7. There was a significant improvement (p<.0001) in the primary outcome (FOSQ score) from baseline to 3 months' post CPAP treatment (15.0 ± 3.3. vs. 16.8 ± 3.3). Significant improvements were also seen in the PHQ-9 (12.4 ± 5.8 vs. 7.1 ± 5.3); ESS (10.6 ± 4.9 vs. 8.0 ± 4.9); EQ-5D Index scores (0.656 ± 0.245 vs. 0.773 ± 0.211), and EQ-5D VAS scores (54.2 ± 22.6 vs. 65.4 ± 22) (all p-values <.0001). Comparing the baseline PSG to on-treatment PSG after 3 months, fAPAP was shown to be efficacious, with AHI, ODI, SaO2 baseline and SaO2 minimum all significantly improving (all p-values <.0001). Total sleep time, total sleep efficiency, and time in slow wave sleep did not significantly change. Participants spent significantly less time in stage 1 sleep (39.1 ± 38.1 vs. 29.4 ± 25.2 minutes, p = 0.015), and significantly more time in REM sleep (39.7 ± 24.0 vs 48.1 ± 24.5 minutes, p = 0.022). Average daily usage was 4.9 ± 2.0 hours per night. Conclusion: This data shows a significant quality of life improvement, more REM sleep, and good compliance in female OSA patients after using PAP therapy with a female specific treatment algorithm for 3 months. Support (If Any): Study supported by ResMed